An improved microtiter assay for evaluating anti-HIV-1 neutralizing antibodies from sera or plasma - Chen Yunyun; Zhang Chiyu; Ben Kunlong (BMC Infectious Diseases, 2003)
Abstract Background The anti-HIV-1 neutralizing antibody assay is widely used in AIDS vaccine research and other experimental and clinical studies. The vital dye staining method applied in the detection of anti-HIV-1 neutralizing antibody has been used in many laboratories. However, the unknown factor(s) in sera or plasma affected cell growth and caused protection when the tested sera or plasma was continuously maintained in cell culture. In addition, the poor solubility of neutral red in medium (such as RPMI-1640) also limited the use of this assay. Methods In this study, human T cell line C8166 was used as host cells, and 3-(4,5-Dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) instead of neutral red was used as vital dye. In order to avoid the effect of the unknown factor(s), the tested sera or plasma was removed by a washout procedure after initial 3–6 h culture in the assay. Result This new assay eliminated the effect of the tested sera or plasma on cell growth, improved the reliability of detection of anti-HIV-1 neutralizing antibody, and showed excellent agreement with the p24 antigen method. Conclusion The results suggest that the improved assay is relatively simple, highly duplicable, cost-effective, and well reliable for evaluating anti-HIV-1 neutralizing antibodies from sera or plasma.